PSYCHOMETRIC EVALUATION OF A QUESTIONNAIRE FOR MEASURING FOOD WASTE BEHAVIOUR AND FOOD SECURITY AT THE HOUSEHOLD LEVEL - Wong Liang Tung; Md Mizanur Rahman (The Indonesian Journal of Public Health, 2022)
Introduction: Food waste and food security are two concepts that are often linked together. This study was performed for the psychometric evaluation of a developed questionnaire for measuring food waste behaviour and food security at the household level. Five expert panels conducted content validation for the relevance, clarity, simplicity, ambiguity of each item. Methods: A cross-sectional quantitative research approach was employed for the questionnaire testing in 10 villages in the Samarahan district of Sarawak state. A total of 168 households were interviewed using face-to-face interviews. Data entry and analysis was undertaken using Microsoft Excel version 2016 and the statistical package for social sciences (SPSS, version 27.0), Result: respectively. Four items were improved, and one item was added to the English questionnaire after receiving feedback from the expert panel and respondents. Further refinement was also performed for the Malay version. Cronbach's alpha value varied from 0.713 to 0.961, indicating the reliability of the questionnaire. Conclusion: Overall, the respondents were able to comprehend most of the questions effectively. No problem was raised for the flow and sequence of the questions. Conclusively, the developed questionnaire is unambiguous in its reliability and validity. Nevertheless, further refinement is required before being used in future studies.